Dynamics of HBsAb persistence and associated BCR IgG-H CDR3 repertoire features in ultra-high versus extremely low responders to HBV vaccination - Yang, Ting-Wen; Sun, Li-Na; Zhang, Ting; Pan, Yu-Rong; Li, Jun; Li, Yang-Yang; Han, Zhi-Yong; Sun, Wan-Bang; Yao, Xin-Sheng; He, Xiao-Yan (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the duration of hepatitis B surface antibody (HBsAb) level maintenance and characterize the corresponding IgG-H CDR3 repertoire in volunteers exhibiting either ultra-high or extremely low HBsAb levels following hepatitis B virus (HBV) vaccination.MethodsThis study was designed to monitor the longitudinal changes in HBsAb levels at multiple time points post-vaccination in healthy volunteers exhibiting either ultra-high or extremely low antibody responses following HBV vaccination. Furthermore, we employed high-throughput sequencing technology to conduct a comprehensive analysis of the compositional differences in the IgG-H CDR3 repertoire. Peripheral blood samples were collected at four distinct phases: pre-vaccination, post-second vaccination, post-third vaccination, and during the follow-up period, to characterize the dynamic changes in the antibody repertoire.ResultsThe longitudinal analysis revealed distinct patterns in antibody response kinetics between the two groups. In the ultra-high responder cohort, a peak HBsAb level (25,354 ± 17,993 mIU/mL) was observed following the second vaccine dose. This was followed by a gradual decline, with mean levels stabilizing at 11,356 ± 9,098 mIU/mL post-third dose and 4,229 ± 2,694 mIU/mL at the 4-year follow-up. The ultra-high hepatitis B surface antibody level group (Group H) exhibited a decrease in IgG-H CDR3 diversity after the second vaccination, followed by an increase after the third vaccination. Compared to the extremely low hepatitis B surface antibody level group (Group L), Group H showed higher characteristic immunoglobulin heavy chain variable region V gene (IGHV) usage frequencies in the CDR3 repertoire after both vaccinations than before vaccination. Additionally, the average mutation rate of the IgG-H CDR3 repertoire in Group H was slightly higher than that in Group L after the third vaccination. Notably, multiple samples from Group H revealed common conserved CDR3 region motifs associated with HBV, as reported in the literature: “YGLDV”, “DAFD”, “YGSGS”, “GAFDI”, and “NWFDP”.ConclusionThe prolonged maintenance of ultra-high antibody levels induced by recombinant HBV vaccines in individuals may be closely related to the characteristic IGHV usage and mutation frequency in individual responses. These findings could provide novel insights into the complex mechanisms of HBV vaccines and HBV infection.